Certified Information Security Manager (CISM) Cert Prep (2022): 3 Information Security Program. - Chapple, Mike (linkedin.com, 2022)
Get the detailed information you need to tackle the Information Security Program domain on the Certified Information Security Manager (CISM) exam.